Thought paralysis : the virtues of discrimination - Dalal, Farhad (Explorations in psycho-social studies series., 2012)
"Given the enormous struggles, efforts and money expended on the equalities enterprise, why has more progress not been made? And further, why have things actually become worse in some circumstances? It is argued this has occurred because:- The values of Equality have been bureaucratized, allowing the liberal principle of "live and let live" to be perverted and put in the service of fear and control.- The Diversity discourse has been hijacked by the libertarians and put in the service of increasing profit, under the guise of liberty and inclusivity.- The equality movements have become apolitical, sidetracked into the project of the indiscriminate celebration and preservation of cultures, in lieu of challenging the status quo within cultures as much as between them.- The versions of psychology and sociology that the equality movements have drawn on are over simple.- The attempts to do away with judgementalism and unfair discrimination have ended up vilifying the capacities for judgment and discrimination per se. The book walks the thin line between the apologists who deify "difference" and the zealots and bigots who vilify the different, to argue that to create a fairer world, we need to enhance our capacities for discrimination, not stifle them. Although the work is focussed around equality, it has bigger things to say about the human condition and organizational life in general"--EBL.